Virtual organisations for effective economic and technological sustainable development policies in the commercial Egyptian public banking sector. (5th April 2020) - Dessouky, Naglaa Fathy El
Nowadays, the concept of virtual organisation (VO) denotes a paradigm shift for policymakers and managers targeting to increase the effectiveness of economic and technological sustainable development. Although the growing number of studies devoted to the topic of VO in developed countries, few studies have been directed to study developing countries, especially the MENA region. This study was inspired by the theoretical research framework proposed by Fathy El Dessouky (2011) to examine the relationship between virtual organisations and the effectiveness of economic and technological sustainable development policies in the commercial public banking sector in Egypt. The research examined four distinguished Egyptian commercial public sector banks which have taken serious steps towards e-banking system. A questionnaire with pre-prepared closed-ended questions was distributed to a random sample of 600 employees at the top, middle and executive levels of management but only 500 employees responded to the questionnaire. The results presented and demonstrated the need for specific areas of improvement regarding the VO, in particular, to satisfy the requirements of economic and technological sustainable development policies in developing countries.